Fluorescence assay for acrylamide determination in fried products based on AgInS2/ZnS quantum dots. Issue 18 (27th April 2022) - Muñoz, Raybel; Santos, Eva M.; Guevara-Lara, Alfredo; Vazquez-Garcia, Rosa A.; Islas-Rodriguez, Nery; Rodriguez, Jose A.
Abstract : The synthesis, characterization and application of AgInS2 /ZnS QDs in acrylamide determination are proposed. Two methodologies based on PET and reversible PET processes are evaluated. Abstract : AgInS2 /ZnS quantum dots were synthesized via solvothermal aqueous phase method using 3-mercaptopropionic acid as the stabilizer. AgInS2 /ZnS quantum dots were employed for acrylamide sensing under two strategies: (1) quenching of the fluorescence signal by the synthesis of polyacrylamide under UV light and (2) use of 2-naphthalenethiol for quenching of the fluorescence signal of quantum dots followed by a recovery of the signal after the addition of acrylamide. Both methodologies display adequate limits of detection, 15.6 and 4.8 μg L −1, respectively. However, the 2-napthalenethiol based method exhibited better precision and selectivity compared to the other methodology. Both methodologies were applied for acrylamide detection in fried snack products and acceptable accuracy was obtained using 2-napthalenethiol method.